Quantitative profiling of glycans and glycopeptides: an informatics' perspective. (October 2016) - Walsh, Ian; Zhao, Sophie; Campbell, Matthew; Taron, Christopher H; Rudd, Pauline M
Graphical abstract: Highlights: We discuss widely used, new and interesting software for the annotation of released glycan and glycopeptide profiles. We discuss tools to detect biomarkers from quantitative profiles and interpret them in terms of gene/protein, disease and pathways. A brief opinion on future glycoinformatics is discussed. Abstract : Experimental techniques to identify and quantify glycan structures in a given sample are continuously improving. However, as they advance data analysis and annotation seems to become more complex. To address this issue, much progress has been made in developing software for interpretation of quantitative glycan profiles. Here, we focus on these informatics tools for high/ultra performance liquid chromatography (H/UPLC), mass spectrometry (MS), tandem mass spectrometry (MS n ) and combinations thereof. Software for biomarker discovery, pathway, genomic and disease analysis and a final note on some future prospects for glycoinformatics are also mentioned.